HUBUNGAN KECERDASAN EMOSIONAL DENGAN KEMAMPUAN PEMAHAMAN KONSEP IPA SISWA KELAS IV SD - Sumarli, Sumarli; Anitra, Rien; Agustin, Dina (Elementary School Teacher Education (PGSD), STKIP PGRI Sumenep, 2025)
This study aims to: (1) determine the level of emotional intelligence of grade IV elementary school students; (2) knowing the level of ability to understand science concepts of grade IV elementary school students; (3) knowing the relationship between emotional intelligence and the ability to understand science concepts of grade IV elementary school students. This research method is quantitative research with a correlation approach. The population of this study was all grade IV students of SDN 88 Singkawang. The sampling technique in this study is a saturated sampling technique. The sample in this study was all grade IV students of SDN 88 Singkawang consisting of classes IVA and IVB totaling 46 students. Data collection techniques in this study are test techniques, which test the ability to understand students' science concepts on Energy and Change material and non-test techniques, namely emotional intelligence questionnaires. Data analysis techniques used in the study were descriptive percentage analysis, mean value analysis, and Spearman Rank correlation. The results showed that (1) the level of emotional intelligence of students was high with an overall average percentage of 75.96%, (2) the level of students' ability to understand science concepts was high with an overall average score of 75.88, (3) there was a relationship between emotional intelligence and the ability to understand students' science concepts with tcalculate > ttable = 5.52 > 1.38 and a coefficient of determination of 40.96%. So it can be concluded that there is a relationship between emotional intelligence and the ability to understand science concepts of grade IV elementary school students.